THE STUDY OF THE EFFECTS OF DIFFERENT CHEMICAL COMPOUNDS APPLIED ON LUFFA CYLINDRICA FIBRES WITH THE HELP OF ULTRASONIC ENERGY - (:unkn) unknown (FREUND PUBLISHING HOUSE LTD, 2008)
Among the natural fibres, Luffa cylindrica fibres are the most widely available throughout the world. Luffa fibres are known to have lignocellulosic fibre characteristics. Because of their practical value, studies are being carried out to make them more useful by means of chemical processes. With this aim, through two different processes, conventional and ultrasonic, four different chemical processes were applied. The results obtained were examined with %weight loss values; mechanical properties, morphological characteristics (SEM) followed by FT-IR and X-Ray diffraction spectra properties. Two different processes and four different chemical processes, carried out with formic acid and acetic acid were proved to be successful. The reason for the success of the ultrasonic processes is the strength achieved by sonication. For this purpose formic acid and acetic acid processes were found to adequately modify the fibres surfaces.
Keywords: biofibers; chemical treatment; Luffa cylindrica; ultrasonic energy; SORPTION PROPERTIES; SURFACE TREATMENTS; COMPOSITES